A Graph-Based Approach to Measuring the Efficiency of an Urban Taxi Service System - Xianyuan Zhan; Xinwu Qian; Ukkusuri, Satish V. (IEEE transactions on intelligent transportation systems, 2016)
Taxi service systems in big cities are immensely complex due to the interaction and self-organization between taxi drivers and passengers. An inefficient taxi service system leads to more empty trips for drivers and longer waiting time for passengers and introduces unnecessary congestion on the road network. In this paper, we investigate the efficiency level of the taxi service system using real-world large-scale taxi trip data. By assuming a hypothetical system-wide recommendation system, two approaches are proposed to find the theoretical optimal strategies that minimize the cost of empty trips and the number of taxis required to satisfy all the observed trips. The optimization problems are transformed into equivalent graph problems and solved using polynomial time algorithms. The taxi trip data in New York City are used to quantitatively examine the gap between the current system performance and the theoretically optimal system. The numerical results indicate that, if system-wide information between taxi drivers and passengers was shared, it is possible to reduce 60%-90% of the total empty trip cost depending on different objectives, and one-third of all taxis required to serve all observed trips. The existence of destructive competition among taxi drivers is also uncovered in the actual taxi service system. The huge performance gap suggests an urgent need for a system reconsideration in designing taxi recommendation systems.